Fto-Deficiency Affects the Gene and MicroRNA Expression Involved in Brown Adipogenesis and Browning of White Adipose Tissue in Mice - Justiina Ronkainen (International Journal of Molecular Sciences, 2016)
Genetic variants in the fat mass- and obesity-associated gene Fto are linked to the onset of obesity in humans. The causal role of the FTO protein in obesity is supported by evidence obtained from transgenic mice; however, the underlying molecular pathways pertaining to the role of FTO in obesity have yet to be established. In this study, we investigate the Fto gene in mouse brown adipose tissue and in the browning process of white adipose tissue. We analyze distinct structural and molecular factors in brown and white fat depots of Fto-deficient mice under normal and obesogenic conditions. We report significant alterations in the morphology of adipose tissue depots and the expression of mRNA and microRNA related to brown adipogenesis and metabolism in Fto-deficient mice. Furthermore, we show that high-fat feeding does not attenuate the browning process of Fto-deficient white adipose tissue as observed in wild-type tissue, suggesting a triggering effect of the FTO pathways by the dietary environment.